2004
DOI: 10.1002/art.20520
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of murine lupus using nucleosomal T cell epitopes identified by bone marrow–derived dendritic cells

Abstract: Objective. Systemic lupus erythematosus (SLE) is characterized by the existence of a heterogeneous group of autoantibodies directed against intact nuclear structures, such as nucleosomes. The most prominent of these autoantibodies are those directed against doublestranded DNA (dsDNA) and histones. The majority are of the IgG isotype and show affinity maturation, both of which are known hallmarks of T cell help. Much evidence suggests that the nucleosome is a major candidate autoantigen in SLE. In this study, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 35 publications
0
22
0
1
Order By: Relevance
“…In NZB/W mice, we cannot exclude that the H2B peptide 1-25 does contain a Th cell epitope in addition to one or several B cell epitopes. However, studies by Suen et al (27) and by us (not shown) using NZB/W-derived CD4 + T cells do not support this hypothesis. Autoimmune responses in lupus are usually analyzed at the systemic level but very rarely at the level of affected target organs.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In NZB/W mice, we cannot exclude that the H2B peptide 1-25 does contain a Th cell epitope in addition to one or several B cell epitopes. However, studies by Suen et al (27) and by us (not shown) using NZB/W-derived CD4 + T cells do not support this hypothesis. Autoimmune responses in lupus are usually analyzed at the systemic level but very rarely at the level of affected target organs.…”
Section: Discussionmentioning
confidence: 59%
“…It contains a number of potential sites for posttranslational modifications, including apoptosis-specific ones (1). Using overlapping peptides covering the whole sequence of H2B, CD4 + T cell epitopes have been identified in lupus mice and patients, among which one that is disease-relevant present in residues 10-33 (25,26), and a second one encompassing residues 31-50 (27). Strikingly, however, although a few B cell epitopes recognized by circulating autoantibodies have been identified (28), a systematic identification of H2B B cell epitopes is not available in lupus, neither in mice nor in humans.…”
mentioning
confidence: 99%
“…Nucleosome is one of the major immunogens driving lupus autoimmunity in murine and human SLE (2,5,7,24,25). Critical peptide epitopes from nucleosomal histones are recognized by autoimmune T cells of lupus patients, irrespective of their MHC haplotypes (5-7).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, H4 71-94 also binds strongly to common HLA-DR alleles. T cells reactive to this epitope can be detected in almost all lupus patients, as well as SNF 1 and BWF 1 mice (2,12,13,19,20).…”
Section: Low-dose Peptide Tolerance Therapy Of Lupus Generates Plasmamentioning
confidence: 99%